Experimental study of physical‐chemical properties modification of coal after CO2 sequestration in deep unmineable coal seams. Issue 3 (19th January 2018) - Zhao, Ningning; Xu, Tianfu; Wang, Kairan; Tian, Hailong; Wang, Fugang
Abstract: An initial investigation into the impacts of CO2 storage in unmineable coal seams, with or without enhanced coal‐bed methane recovery (CO2 ‐ECBM), was conducted, focusing on changes in the chemical and physical properties of coal. A high metamorphic grade anthracite was obtained from Qinshui Basin in China. Powdered coal was reacted with deionized water and carbon dioxide at temperatures of 25–35 °C and pressures of 5–11 MPa, in seven custom‐built batch reactors – conditions similar to the in situ formation conditions for the coal samples. An experiment with N2 saturated‐water to compare CO2 ‐free‐water mobilization with CO2 ‐water was also performed. It was observed that the supercritical CO2 ‐H2 O‐coal reaction had a more significant influence on the micropores than mesopores. The micropore increase was reflected directly in the specific surface area and pore volume, which increased sharply. The true density also increased accordingly. The changes to the pore structure in the coal may affect the storage capacity of CO2 and can modify the fluid flow pattern in the process of CO2 ‐ECBM. Meanwhile, after exposing the coal samples to supercritical CO2, most of the trace‐element content in the reaction solutions was very low; only the Se and Mn content was beyond acceptable drinking water quality, but not enough to produce a serious influence on shallow aquifers. Nonetheless, the potential for mobilizing toxic trace elements from the coalbed is an important factor to be considered when evaluating CO2 sequestration in deep unmineable coal seams. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd.